2017
DOI: 10.1080/19476337.2017.1368717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion on the carotenoid content, physical and sensory properties of snacks added with bagasse of naranjita fruit: optimization process

Abstract: (2018) Effect of extrusion on the carotenoid content, physical and sensory properties of snacks added with bagasse of naranjita fruit: optimization process, CyTA -Journal of Food, 16:1, 172-180, DOI: 10.1080/19476337.2017 To link to this article: https://doi.org/10. 1080/19476337.2017 Extruded third-generation snack foods (TGS) can be produced adding materials rich in bioactive compounds, such as the bagasse of naranjita fruit (Citrus mitis B.). The aim of this work was to study the effect of extrusion tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
5
19
0
1
Order By: Relevance
“…The obtained results showed that the dehydrated NB presented the highest values of crude fiber and ash content. These values are similar to those reported in previous studies of this fruit (Ruiz‐Armenta et al, ). Also, NB presented the lowest values of pH and highest values of TA.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results showed that the dehydrated NB presented the highest values of crude fiber and ash content. These values are similar to those reported in previous studies of this fruit (Ruiz‐Armenta et al, ). Also, NB presented the lowest values of pH and highest values of TA.…”
Section: Resultssupporting
confidence: 92%
“…The level of NB (8.02%) was obtained from optimal conditions reported in a previous work (Ruiz‐Armenta et al, ), while 6% of MP was the result of preliminary tests using CS:CF ratios of 1.5:1, for which the snacks showed improved sensory properties. All mixtures were processed, separately, according to optimal extrusion conditions (extrusion temperature = 125°C, moisture content = 23%, screw speed = 75 rpm, and compression ratio 1:1) reported by Ruiz‐Armenta et al (). In this process a single screw laboratory extruder with three heating zones and 20:1 barrel length‐to‐diameter ratio (Brabender 20DN, model 8‐235‐00, O‐HG Brabender, Duisburg, Germany) was used.…”
Section: Methodsmentioning
confidence: 99%
“…The 3G sample with 9% of hemp had the lowest values for crispiness and the highest values for fracturability, but nevertheless, it was still graded as a tasty snack with acceptable properties. In other research, increasing the content of the added fruit component (rich in fiber, flavonoid compounds) decreased the sensory acceptability of the product (Choi, Phillips, & Resurreccion, ; Ruiz‐Armenta et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…In Figure 3(b) is shown an increase in color b* values of breakfast cereals as DNP levels were increased, in all ET range. This behavior could be due to a high content of carotenoids (2.3 ± 0.49 mg/g db) in DNP (Ruiz-Armenta et al, 2018), which provides the yelloworange coloration to this pomace. Also, at high levels of ET and DNP, the BC presented high color b* values.…”
Section: Color Parameters B* and L*mentioning
confidence: 94%
“…However, an important content of bioactive compounds remains in pomace (Delgado-Nieblas et al, 2017). In addition, the pomace possesses a citrus flavor and an attractive orange coloration that may result appropriate for the production of different extruded products, such as snacks foods (Ruiz-Armenta et al, 2018), and breakfast cereals with good sensory acceptability.…”
Section: Introductionmentioning
confidence: 99%